PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN PENERAPAN METODE DEMONSTRASI SISWA KELAS V SD NEGERI 001 UKUI KECAMATAN UKUI - Yusuf, Marni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low results of students' mathematics learning, of 28students only 14 students who completed and the average value obtained was 65. To theresearchers conducted the study by applying the method of demonstration. This research is aclass act who performed a total of two cycles, the data used in research activities as well asteacher and student learning outcomes in mathematics. The research was conducted inclasses V SD Negeri 001 Ukui Kecamatan Ukui. Based on the results of research conducteddata showed that the results learn some vital lessons and activities of teachers and studentsmenglami increase in each cycle. This is evidenced by: (a) the activities of teachers hasincreased in each cycle, the first cycle of meetings I obtain a score of 13 (46.42%), in the firstcycle of meetings II given a score of 18 (64.28%), the second cycle meeting I obtained a scoreof 20 (71.42%). And the second cycle II meeting obtain a score of 26 (92.85%). Activities ofstudents has increased at each meeting in each cycle. At the meeting I cycle I obtained a scoreof 12 (42.85 %%), the second meeting of the second cycle obtain a score of 19 (67.85%), at ameeting I cycle II obtained a score of 21 (75.00%). And at the second meeting of the secondcycle obtain a score of 25 (89.85%); (B) the results of learning mathematics increased ineach cycle, the preliminary data of students who achieve mastery only 50% with an averagevalue of 65, the first cycle increased to 70% with an average of 69.25 and completenessclasses in the second cycle reached 85% with an average value of 74.5.